Pengembangan Sistem Absensi Berbasis Web Bagi Mahasiswa Magang dengan Menggunakan Coordinate Point Validation - Fadlan, Muhammad Fadlan Alamsyah; Khaila, Khaila Mukti Harahap (Yayasan Pendidikan Al-Yasiriyah Bersaudara, 2024)
This study aims to develop a web-based attendance system with check-in and check-out features validated using geolocation for internship students at the Organization Division of the Regional Secretariat of Binjai. The main issue identified at the research site is the inefficiency and inaccuracy of attendance tracking, which is still conducted manually and prone to recording errors. To address this issue, the study adopted the Waterfall methodology, which includes the stages of requirements analysis, system design, implementation, testing, and maintenance. The results indicate that the developed attendance application can accurately record attendance by validating geographic locations. Key features implemented in the system include user authentication, data encryption to protect personal information, and geolocation validation to ensure attendance can only be recorded at authorized locations. System testing demonstrated high accuracy in recording attendance in areas with adequate GPS signals. However, in areas with weak signals, geolocation accuracy needs improvement. The application is also equipped with a reporting feature, enabling real-time monitoring of attendance data. Overall, this attendance system not only enhances the efficiency and accuracy of attendance tracking processes but also supports data transparency and security. Further development is recommended to improve performance in areas with weak signals and to incorporate advanced analytics features for attendance reporting.